Regional climate change and its effects on river runoff in the Tarim Basin, China - Chen, Yaning; Takeuchi, Kuniyoshi; Xu, Changchun; Chen, Yapeng; Xu, Zongxue (Hydrological processes, 2006)
The hydrological response to climate change in the Tarim River Basin was investigated by analysing the hydrological, temperature and precipitation data of the past 50 years. The long‐term trend of the hydrological time‐series, including air temperature, precipitation, and streamflow, was examined by using both parametric and non‐parametric techniques and the plausible association between streamflow and climate change by the method of grey correlation analysis. The results show that the study area became warmer in the last few decades. The air temperature experienced a significant monotonic increase by 5%; the precipitation showed a significant decrease in the 1970s and then a major increase in the1980s and 1990s, with average annual precipitation up by 6·8 mm per decade. A step change occurred in both temperature and precipitation around 1986, with mean temperature and precipitation increasing from 6·7 °C and 146 mm before 1986 to 7·3 °C and 180 mm respectively after 1986. The temperature has risen by nearly 1 °C over the past 50 years, possibly resulting from the impact of global climate change. Streamflows in the Aksu River and the Yarkant River have shown a significant (P < 0·05) tendency of increase. This is particularly the case for the Aksu River. The coefficients of streamflow increase in the Aksu and Yarkant Rivers are 0·41 and 0·13 respectively. The results of grey correlation analysis show that in the Aksu River, which is located in the northwest of the basin, the impact of precipitation on streamflow is much greater than that of temperature. However, in the Hotan River, which is located in the southwest of the basin, the impact of temperature on streamflow is much greater than that of precipitation. This is likely to be related to the geographic distribution of the headstreams of the rivers. Copyright © 2006 John Wiley & Sons, Ltd.